Atypical And Severe Enlargement Of Right Atrium - Siniscalchi, Carmine; Rossetti, Pietro; Rocci, Anna; Rubino, Pasquale; Basaglia, Manuela; Gaibazzi, Nicola; Quintavalla, Roberto (Acta Biomedica Atenei Parmensis, 2016)
A 76 year-old woman was admitted to the Emergency Department for recent-onset dyspnea and cough. The electrocardiogram was considered inconclusive. A thoracic X-ray showed global cardiac profile enlargement. Computed tomography, acutely performed in the clinical suspicion of atypical pneumonia/myocarditis or pericardial effusion, showed cardiac enlargement especially of the right chambers. In order to investigate Ebstein’s anomaly, pericardial cysts, tumors or other conditions of the right heart a simple trans-thoracic echocardiogram was performed. Four chambers view showed a giant right atrium aneurysm with moderate tricuspid regurgitation without stenosis or typical Ebstein’s echocardiographic pattern.